Factors That Affects the Implementation of Training and Development in Small Business: Case of Manufacturing Industry in Johor, Malaysia - S., Sasitharan (2011)
The Malaysian government has realized that it is necessary to increase the competitiveness of small and medium enterprise (SME) in domestic and global market. Basically, training and development programs playing important role in supporting small business to be achieve success. There are some important variables which are the critical factors in decision making of whether to implement training in the organizations. Thus, to identify this issues the researcher done a research to find out those are the factors influencing in implementation of training in an organization. This study was carried out in manufacturing industry in Johor state by use of questionnaire. Then the data analysis was carried out by using descriptive and factor analysis method. The results shows ownership and management role has a strong relationship in determine the implementation of training in SME organization. Apart from that, the influence levels of other three factors towards implementation of training are neutral. Based on the finding there some recommendation and conclusion provided.